Contamination of Date Fruit by a Flatoxigenic Fungi and a Flatoxins in Hilla City, Iraq - Mohammad J. Al-Jassani (Journal of Global Pharma Technology, 2018)
The present study aim to evaluate the incidence of fungi (Mainly Aspergillus sp) and Aflatoxins (AFs) contamination in Date fruit Total of 9 most common Date samples belongs to type Zahidi and Shwaythee in addition to date syrup, were collected from the local market of Hilla city and from the general company for Date manufacturing and marketing. Intergenic fungi were isolated by direct plate method and were morphologically identified on specified media. Aflatoxins production by Aspergillus spp. were screened and determined by thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). Date samples were analyzed by HPLC for AFs contamination. Total of 158 isolates were isolated from Date samples belonging to different fungal genera. Aspergillus spp. represented 84% of the total isolated mold species. Aspergillus niger was dominant (65%) and A. flavus was only 19%. Of the total A. spp., 16.6% found active in aflatoxin B1 (AFB1) and aflatoxin B2 (AFB2) production among of which 45.45% belong to A. Niger and 54.54% belong to A. flavus. HPLC shows that 88.8 % of dates fruit samples tested positive for aflatoxins (AFs). As a first report by this study, AFs (AFB1 and AFB2) were detected produced by A. niger isolates by TLC. This is the first report through this study that AFG is produced by both A. niger and A. flavus as detected by HPLC. The results showed that Date fruits are contaminated with total AFs ranged from 5.7 to 274µg/kg.Keywords: Date fruit, Aflatoxin, Aspergillus, TLC, HPLC.